KUAT TEKAN BETON MUTU TINGGI DENGAN PENAMBAHAN CONPLAST SP 337 - Rusman Asri; Sartika Nisumanti (Jurnal Tekno Global, 2014)
Concrete is one of the building materials are very useful in the construction, where concrete is a mixture ofPortland cement (PC) or other hydraulic cement composition includes a mixture determined between fineaggregate, coarse aggregate and water, with or without the use of additional materials. The study was conductedto determine the compressive strength of concrete and other specifications that concrete is achieved by theaddition of Conplast SP 337. That is done using a cube-shaped test specimens measuring 15 cm x 15 cm x 15 cmwith 5 (five) variation of mixture B1, B2, B3, B4, and B5, each four (4) specimens. for each test age of 3 days, theage of 7 days, 14 days, 21 days and 28 days. From the research, it was found that the compressive strength ofconcrete with each stir the mixture obtained 1.2: 2: 3 (B5) compressive strength greater of 4.5% of thecompressive strength of normal concrete specimen (B1). And the compressive strength of the mortar 1: 2,5: 3 withthe addition of SP 337 (B5) is lower than the compressive strength of normal concrete specimen (B1) amounted to23.71%.